2021
DOI: 10.1002/wnan.1749
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances and applications of microspheres and nanoparticles in transarterial chemoembolization for hepatocellular carcinoma

Abstract: Transarterial chemoembolization (TACE) is a recommended treatment for patients suffering from intermediate and advanced hepatocellular carcinoma (HCC). As compared to the conventional TACE, drug‐eluting bead TACE demonstrates several advantages in terms of survival, treatment response, and adverse effects. The selection of embolic agents is critical to the success of TACE. Many studies have been performed on the modification of the structure, size, homogeneity, biocompatibility, and biodegradability of embolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 182 publications
0
17
0
Order By: Relevance
“…There are studies comparing the treatment efficacy and complication rates according to the size of drug-eluting beads (15). Higher coagulation necrosis and complete response rates, longer overall survival, less fibrosis, and postembolization syndrome have been reported in embolization procedures performed with 100-300 μm particles compared to those undertaken with larger particles (15). However, due to the risk of severe necrosis in normal liver tissue, advanced embolization with very small particles should be avoided (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are studies comparing the treatment efficacy and complication rates according to the size of drug-eluting beads (15). Higher coagulation necrosis and complete response rates, longer overall survival, less fibrosis, and postembolization syndrome have been reported in embolization procedures performed with 100-300 μm particles compared to those undertaken with larger particles (15). However, due to the risk of severe necrosis in normal liver tissue, advanced embolization with very small particles should be avoided (11).…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the risk of severe necrosis in normal liver tissue, advanced embolization with very small particles should be avoided (11). While no significant difference has been shown between large and small size particles in terms of drug release, it has been reported that small beads have a higher drug-eluting capacity due to their high surface area/volume ratio (15). Many factors such as tumor volume, size of the artery feeding the tumor, and tumor characteristics should be considered in the selection of the bead size to be used.…”
Section: Discussionmentioning
confidence: 99%
“…This approach does not require ethiodol and lowers pain and systemic toxicity in the patients. Some shortcomings of DEB-TACE are permanent occlusion (due to nondegradable microspheres), a limited selection of therapeutics to load onto the microspheres, and nontraceability of microspheres during in vivo applications [ 62 ]. The development of new degradable microspheres with the ability to load more than one therapeutic candidate may expand treatment options.…”
Section: Endovascular Embolizationmentioning
confidence: 99%
“…Therefore, the visualization of drug loaded microspheres and the search for new drug carriers have become a research hotspot (Sharma et al, 2016;Liu et al, 2021;Jia et al, 2022). At present, research on the visualization of microspheres mainly focuses on X-ray and magnetic resonance imaging (MR imaging).…”
Section: Introductionmentioning
confidence: 99%
“…MR imaging is mainly achieved by introducing paramagnetic lanthanides and superparamagnetic iron oxide into the microspheres (Fidelman et al, 2002). Some researchers have also studied CT/MRI dual-imaging microspheres with both CT and MRI internal contrast agents, which have been preliminarily verified in animal experiments (Hagit et al, 2010;Jia et al, 2022;Yin et al, 2022). Although previous studies have realized the visualization of drug loaded microspheres to a certain extent, they have not comprehensively solved the monitoring of drug loaded microspheres during injection, postoperative CT and MRI reexamination, or of distribution tracking.…”
Section: Introductionmentioning
confidence: 99%